P650 Integrin expression patterns of patients with IBD treated with vedolizumab. (30th January 2023) - Kokkotis, G; Chalakatevaki, K; Papathanasiou, E; Tzanoudaki, M; Kane, R; Liatsis, M; Zampeli, E; Michopoulos, S; Bamias, G
Abstract: Background: Anti-α4β7 integrin monoclinic antibody vedolizumab is an effective treatment for moderate and severe Ulcerative Colitis and Crohn's Disease. Occasionally vedolizumab-treated patients experience articular extraintestinal manifestations, in the form of arthralgias, which could be attributed to lymphocyte tracking modification caused by vedolizumab. This study aims to describe α4β7 andα4β1 integrin expression on circulating lymphocytes and the effect of vedolizumab on integrin expression, as well asto identify expression patterns associated with arthralgias under vedolizumab. Methods: A cross-sectional study was conducted. Peripheral blood was collected in EDTA-coated bottles before a scheduled drug administration. Expression of α4β7 and α4β1 integrins on CD4+T, CD8+T, B and plasma cells was studied by flow cytometry (DX Flex, BC), using CD3, CD4, CD8, CD19, CD138, CD49d (α4), β7, CD29 (β1). Kaluza C software and SPSS23 were used for analysis. Results: In total, 40 IBD patients (16 of them treated withvedolizumab) and 8 healthy controls were included. There was a higher percentage of α4β1expressing lymphocytes compared to α4β7+ ones ( P <0.001) (figure 1). Vedolizumab-treated patients had lower percentages of integrin-expressing B cells (α4β7 P =0.001 vs controls, α4β7 P =0.052 vs non-vedolizumab IBD, α4β1 P =0.002 vs controls, α4β1 P =0.015 vs non-vedolizumab IBD) and α4β1 plasma cells ( P =0.013 vs non-vedolizumab IBD) (figure 2). In patients treated with vedolizumab with arthralgias, α4β7 expression on B-cells was more suppressed, whereas α4β1 expression on plasma cells was less suppressed, compared to those that had not developed arthralgias, but not in a statistically significant level (figure 3). Conclusion: Patients treated with vedolizumab presented different patterns of integrin expression on circulating B cells. Manifestation of arthralgias under vedolizumab may be associated with a disruption of α4β7/α4β1 proportion. Funding: This study was funded through a research grant from the Greek IBD study group (EOMIFNE) to G.B. EOMIFNE Grant: 2020EOMIFNEp1